The Role of Therapeutic Anticoagulation in COVID-19 - Ruth McGovern; Patrick Conway; Isabell Pekrul; Omar Tujjar (Case Reports in Critical Care)
Coagulopathy has proven to be a common complication of the novel coronavirus SARS-CoV-2, with evidence of elevated D-dimers and fibrin degradation products associated with an increased incidence of thromboembolism. Despite emerging evidence describing the coagulopathy and its clinical relevance in COVID-19, fewer studies have addressed the potential role of empiric therapeutic anticoagulation in this setting. We report the case of a patient admitted to our intensive care unit (ICU) with severe acute respiratory distress syndrome (ARDS) secondary to COVID-19 whose clinical trajectory improved dramatically after initiation of a therapeutic dose of LMWH. The patient showed progressive elevation of fibrinogen and D-dimers despite a prophylactic dose of LMWH during her ICU stay. This was met with a moderate increase of troponin T-hs, an escalating need for vasopressors, and a progressive decrease in her P/F ratio despite preserved lung static compliance. Her platelet count was normal and had an elevated fibrinogen during the first week of ICU stay. The ECG was normal, and a bedside transthoracic echocardiogram showed no evidence of pulmonary embolism and a preserved EF with no regional wall motion abnormalities (RMWA). The chest X-ray was not dissimilar to previous exams, and the ABG showed hypoxia with normal pCO2 values. The decision was made to commence empiric therapeutic enoxaparin. The patient did not experience bleeding complications, and her clinical trajectory appeared to change dramatically. She was successfully extubated three days later and proceeded to clinical recovery and eventual discharge from the ICU. The available evidence shows that there is undoubtedly coagulopathy associated with COVID-19 with various subsequent forms of clinical manifestation described in the literature. Evidence also shows the benefits of heparin as an anticoagulant. From the discussion of this case report, however, it can be concluded that despite the plausible theoretical rationale, studies pertaining to the role of empiric therapeutic anticoagulation in this setting fall short of providing compelling evidence. Subsequently the role of empiric therapeutic anticoagulation in COVID-19 remains unclear with a pressing call for further research.